Pelatihan Keterampilan Menyajikan Presentasi Menarik Microsoft Power Point pada Guru SD Kecamatan Salo - Afriza Rahma Rani; Romi Laspita (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
Current teaching and learning activities must be supported by utilizing Microsoft power point. The purpose of this service is to train teachers to have the skills to use Microsoft power point in learning, assist teachers in designing lessons and instructions on making lessons interactive and interesting using Microsoft power points and teachers are able to optimally utilize the digital era as a support for the learning process. . The implementation of the service training was carried out at the Salo District Elementary School.